**Part B) only**

Show that for integers k and n such that `1<=k<=n` ,

A)

`k^nC_k = n ^(n-1)C_(k-1)`

B)

Hence or otherwise prove that for any `x in RR` and n>=0,

`sum_(k=0)^n k^nC_kx^k (1-x)^(n-k) = nx`

### 1 Answer | Add Yours

we know that;

`k(^nC_k) = n(^(n-1)C_(k-1))`

`sum_(k=0)^n k (^nC_k) x^k (1-x)^(n-k)`

`=sum_(k=1)^n k (^nC_k) x^k (1-x)^(n-k)` When k = 0 first term is 0.

`=sum_(k=1)^n n[^(n-1)C_(k-1)] x^k (1-x)^(n-k)`

`=nxsum_(k=1)^n [^(n-1)C_(k-1)] x^(k-1) (1-x)^((n-1)-(k-1))`

let k-1 = j

Since at start k = 1 then at start j = 1-1 = 0

`=nxsum_(j=0)^(n-1) [^(n-1)C_j] x^j (1-x)^(n-j)`

Using binomial theorem we know that;

`(a+x)^n = sum_(r = 1)^n^nC_ra^rx^(n-r)`

Similarly;

`=nxsum_(j=0)^(n-1) [^(n-1)C_j] x^j (1-x)^(n-j)`

`=nx[(x+(1-x))^(n-1)]`

`=nx`

*So the answer is obtained as required.*

**Sources:**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes